Tren Penelitian Tentang Tantangan dan Peluang Implementasi Pendekatan Deep Learning dalam Kurikulum Merdeka - Syafarotul Ainiyah; Ach Wildan Hoironi; Agung Setyawan (CV. SINAR HOWUHOWU, 2025)
The purpose of this study is to determine research trends related to the application of deep learning as well as the challenges and opportunities that arise from implementing a deep learning approach in an independent curriculum. The researcher used a quantitative method. The instrument used was Nvivo, which was used to analyze keywords, publication year, and the number of citations for each article. This article reviews various literature and research results from recent years to identify the year, citations, and keywords, as well as frequently appearing recommendations related to this. The calculation of the test results processed by the researcher resulted in the development of research interest related to the challenges and opportunities of the deep learning approach, namely in 2022-2025. In this study, there were five articles that had no citations, and of the 15 articles, there were keywords focused on several words, namely deep learning, learning, education, independent curriculum. It can be concluded that the application of this deep learning approach has been optimally implemented in Indonesia. On the other hand, deep learning as part of artificial intelligence has great potential to support personalized learning, analysis of student learning data, and the provision of more effective feedback. However, its implementation in educational environments, especially in Indonesia, still faces various obstacles such as limited infrastructure, lack of training for teachers, and gaps in technological knowledge. Behind these challenges lies a great opportunity in their implementation, namely that students have a sense of enthusiasm in developing new ideas.